ENHANCING INFORMATION LITERACY SKILLS ROUGH THE IMPLEMENTATION OF THE EMPOWERING 8 MODEL FOR THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS - Rachman, Reza Saeful; Zaelani, Pupi Indriati; Sidik, Adi Permana; Irma, Neng (PT Altin Riset Publishing, 2024)
The 2030 Sustainable Development Goals (SDGs) are global goals set by the United Nations to achieve sustainable progress and improve people's quality of life. In the era of digital transformation, information literacy is an important key in achieving the SDGs. In the context of education, literacy plays an important role in achieving the SDGs. This article aims to review various literature on improving information literacy skills through the Empowering Model in the success of the Sustainable Development Goals. The method used by the author is the literature study method. The literature study in this research was taken from various sources, including scientific journals, books, and other literature. The result of this literature study is an empowering 8 model that can be implemented in schools and outside schools to improve the quality of community literacy. The empowering 8 information literacy model includes the ability to identify, explore, select, organize, create, present, assess, and apply information that can benefit individuals and society.